1998
DOI: 10.1063/1.367922
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties and ordering in C-coated FexCo1−x alloy nanocrystals

Abstract: C-coated FexCo1−x (x=0.50, 0.45, 0.40, 0.35, 0.30, 0.25) nanoparticles were produced using a rf plasma torch. The only C source was acetylene used as a carrier gas. Structural determination by x-ray diffraction indicated a single disordered bcc α-FeCo phase along with graphitic C for all compositions. A Scherrer analysis of the peak widths revealed particles to have an average diameter of 50 nm. A broad log-normal size distribution was found from transmission electron microscopy observations. Magnetic hysteres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
38
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 7 publications
5
38
0
Order By: Relevance
“…4, showing a drop in the carbon content of the samples by decreasing the CO fl ow rate. Raman spectra of the FeCo/GC core-shell nanoparticles synthesized at different gas fl ow rates can be seen in Figure 4 b, indicating a sharp graphitic carbon G-band and a disordered D-band.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…4, showing a drop in the carbon content of the samples by decreasing the CO fl ow rate. Raman spectra of the FeCo/GC core-shell nanoparticles synthesized at different gas fl ow rates can be seen in Figure 4 b, indicating a sharp graphitic carbon G-band and a disordered D-band.…”
Section: Resultsmentioning
confidence: 97%
“…[ 1,2 ] Among various magnetic nanoparticles that have been studied for potential biomedical applications, FeCo nanoparticles are promising candidates because of their high saturation magnetization and high Curie temperature. [3][4][5] However, the ease of oxidation, dissolution in acidic environments, and potential toxicity of these materials in their native state restrict their use in biomedical applications. [ 3,6,7 ] A graphitic surface coating not only would address each of these issues, thereby rendering them biocompatible and improving their thermal stability but also would act as a powerful link to covalently attach organic molecules (i.e., drugs) to the magnetic cores.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the well-known Slater-Pauling curve [1], it is expected that Fe-Co alloy with a specific composition exhibits the largest magnetic moment among various iron group alloys. The Fe-Co alloys are popularly used soft magnetic materials [2,3] for ultrahigh-density magnetic recording media because of their relatively low coercive fields. There was also a report on possible nanoscale applications by forming Fe-Co nanowires in self-assembled arrays [4].…”
mentioning
confidence: 99%
“…Other studies have shown that encapsulation of magnetic nanoparticles in carbon can enhance oxidation resistance and increase nanostructure stability. [6][7][8] This article details the effect of carbon on the magnetic properties and oxidation resistance of (SmCo 5 ) x :C 1Ϫx with 0.15рxр1.…”
Section: Introductionmentioning
confidence: 99%